Sara Cwynar : Glass Life. - Heti, Sheila; Russell, Legacy; Bouthillier, Rose (New York, NY : aperture, 2021)
Soft Film ; Rose Gold ; Red Film
An investigation of color and image-driven consumer culture, Glass Life brings together Sara Cwynar’s multilayered portraits and stills from the films Soft Film (2016), Rose Gold (2017), and Red Film (2018). Cwynar’s research-driven and visually complex images constitute the hallmarks of contemporary post–Pictures Generation work—in which photography is pursued in relation to film, sculpture, digital culture, and the cultural and technological history of image-making. Cwynar’s work revolves around her interest in subjective notions of beauty through images; the fetishization of consumer objects and colors; and the exploration of the informal image archives that have emerged around the industrialization and capitalization of these ideas. As part of her core practice, Cwynar collects, arranges, and archives her eBay purchases and creates studio studies of these consumer objects, exploring how images circulate online and how the lives and purposes of both physical objects and their likenesses change over time. Sara Cwynar: Glass Life is a must-have sourcebook for understanding the multilayered practice of this celebrated, multidisciplinary artist. (provided by publisher)
boek
Keywords: Cwynar, Sara